Tablice do Obliczania Powierzchni Wpływowych dla Pasma Płytowego - Kaczkowski, Z.; Żórawski, M. (Engineering Transactions, 1959)
This paper contains 15 numerical tables for computing the ordinates of the influence surfaces for geometric and mechanical quantities of a plate strip. Using these tables, we can find deflections, moments and shear forces in a plate subjected to the action of concentrated moments, axially symmetric loads, or loads uniformly distributed along a straight line segment. Numerical examples concerning girderless floor illustrate the use of the tables.